Songs of Willow Frost : a novel - Ford, Jamie (Ballantine Books, 2013)
With his friend Charlotte, twelve-year-old William Eng, a Chinese-American boy, escapes from a Seattle orphanage determined to find his mother Willow and discover his connection to the exotic film star.